Tantangan dan Strategi Guru dalam Proses Belajar Mengajar selama Covid-19 - Siregar, Eva Fitri Y; Sitorus, Nurhayati; Lestari, Febrika Dwi; Oktapiani, Tamara; Pakpahan, Sulastri (BASIS (Bahasa dan Sastra Inggris), 2022)
This research is conducted because of Covid-19 that has been going on for almost 2 years and it affect to the teaching learning process at SMA Negeri 1 Siborongborong. The objective of research is to know and describe challenges and strategies faced by English teacher in online learning (OL) as long as pandemic. In this research, the research used qualitative research. The source of data came from 3 English teachers at SMA Negeri 1 Siborongborong. The technique that used to collect data by using questionnaire. The data was analysed by using Miles and Huberman model. Three stages were used in analysing data, namely data reduction, displaying data and drawing conclusion/verification. The result of the research showed that teachers’ undergone several challenges at SMA Negeri 1 Siborongborong, namely; (1) uneven network, (2) limited facility, (3) student learning lost, (4) Students were not so serious to the lesson and (5) willing to explain the explanation two or three times. whereas, teacher’s strategies were used English teacher in SMA Negeri 1 Siborongborong during OL were; (1) Teacher did not force the students to have too much (2) Limiting the material and homework (3) motivating and supporting the students (4) Inviting student to joke so they don’t get bored right away (5) Trying to present interesting learning process for students. So, it can be concluded that network affects to the students’ ability in understanding the material in the classroom.